The ethical value of compassion: A dialogue between Kant and Schopenhauer - Pessis, Begoña (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The purpose of this article is to discuss the positions of Kant and Schopenhauer on the ethical value of compassion. In short, my proposal is that compassion is a necessary condition of ethics, but not a sufficient one. A careful consideration of the arguments from both authors and the examination of two problems that arise from their confrontation will lead us to conclude, at least plausibly, that to dispense with compassion in ethics is as misguide as to make it the only moral motive.